Efficacy and Safety of Sophora flavescens (Kushen) Based Traditional Chinese Medicine in the Treatment of Ulcerative Colitis: Clinical Evidence and Potential Mechanisms - Chen, Mingjun; Ding, Yuxuan; Tong, Zhanqi (Frontiers in Pharmacology, 2020)
Background: Sophorae flavescentis (Kushen), a kind of Chinese herb, is widely used in the treatment of ulcerative colitis (UC) with damp-heat accumulation syndrome (DHAS) according to traditional Chinese medicine (TCM) theory. Objective: The aim of this study was to illuminate clinical efficacy and potential mechanisms of Kushen-based TCM formulations in the treatment of DHAS-UC. Materials and Methods: A systematic literature search was performed in PubMed, EMBASE, Chinese Biomedical Literature database, China National Knowledge Infrastructure database, Chongqing VIP Information database, and Wanfang database for articles published between January 2000 and July 2020 on randomized controlled trials that used Kushen-based TCM formulations in the treatment of DHAS-UC. A network pharmacology approach was conducted to detect the potential pathways of Kushen against DHAS-UC. Results: Eight RCTs with a total of 983 subjects were included in the meta-analysis. Compared with the control subjects (5-aminosalicylic acid therapy), those who received Kushen-based TCM formulations for the treatment of UC showed a significantly higher clinical remission rate (OR=1.45, 95% CI: [1.07, 1.95], P=0.01) and lower adverse events (OR=0.59, 95% CI: [0.35, 1.00], P=0.05). Component-target-pathway network was constructed and indicated five main components (Quercetin, Luteolin, Matrine, Formononetin and Phaseolin), three major targets (Interleukin-6, Myc proto-oncogene protein, and G1/S-specific cyclin-D1) and one key potential therapeutic pathway (PI3K-Akt signaling) of Kushen against DHAS-UC. Conclusions: Kushen-based TCM formulations provide good efficacy and possess great potential in the treatment of UC. Large-scale and high-quality clinical trials and experimental verification may be considered for further confirmation of the efficacy of Kushen-based formulations.